2006
DOI: 10.1007/s10661-005-9140-2
|View full text |Cite
|
Sign up to set email alerts
|

Soilaluminum, Iron, and Phosphorus Dynamics in Response to Long-Term Experimental Nitrogen and Sulfur Additions at the Bear Brook Watershed in Maine, USA

Abstract: Atmospheric deposition of nitrogen (N) and sulfur (S) containing compounds affects soil chemistry in forested ecosystems through (1) acidification and the depletion of base cations, (2) metal mobilization, particularly aluminum (Al), and iron (Fe), (3) phosphorus (P) mobilization, and (4) N accumulation. The Bear Brook Watershed in Maine (BBWM) is a long-term paired whole-watershed experimental acidification study demonstrating evidence of each of these acidification characteristics in a northeastern U.S. fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…In agreement with other studies we found that microbial biomass P is large in comparison to extractable P (Walbridge et al 1991). Sherman et al (2006) hypothesized that soil acidity arising from atmospheric deposition could increase mobilization of Al and Fe along with any bound P, and that changes in P would depend upon forest type. In hardwood forests, biotic uptake of mobilized P prevents P loss.…”
Section: Links Among Biogeochemical Cycles With N Fertilizationsupporting
confidence: 93%
“…In agreement with other studies we found that microbial biomass P is large in comparison to extractable P (Walbridge et al 1991). Sherman et al (2006) hypothesized that soil acidity arising from atmospheric deposition could increase mobilization of Al and Fe along with any bound P, and that changes in P would depend upon forest type. In hardwood forests, biotic uptake of mobilized P prevents P loss.…”
Section: Links Among Biogeochemical Cycles With N Fertilizationsupporting
confidence: 93%
“…as reported by Sherman et al (2006) in a study about long-term acidification in spodic forest soils in Maine, USA. However, we also suggest analyzing the spatial patterns of P binding partners to explain the heterogeneity of P fractions in soil during pedogenesis.…”
Section: Factor Analysis 20supporting
confidence: 65%
“…This difference in extractable P was attributable to the relatively low abiotic affinity for P in organic soil materials, compared to the high P fixation capacity typical of acidic Al-and Fe-rich forest soils where P cycling has been demonstrated to be highly vertically stratified (Wood et al 1984;Yanai 1992). The only significant differences in concentrations potentially attributable to treatments were for lower extractable P concentrations in the WB 25-C cm-depth increment, which could be attributable to P depletion with metal mobilization in these soils as a result of acidification (Sherman et al 2006;SanClements 2009).…”
Section: Bbwm Soil Chemistry-2006mentioning
confidence: 89%